Immaterial Losses in Breach of Contract Lawsuit in Indonesia - Seyla Missy Togito Silitonga; Abdul Salam (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
One of the reasons for filed Breach of Contract’s lawsuit to the Court is to demand compensation as one of the legal consequences that must be fulfilled by the debtor to creditors who suffered losses, both material and immaterial losses which have actually occurred or could be expected to occur at the time the contract was made as well as the profits that could have been obtained by the creditor. In Indonesia, there are still debates related to the fulfillment of immaterial losses in breach of contract cases. Therefore, authors conduct normative legal research using the statute and case approach in order to examine the issues. This research indicates that the immaterial losses in breach of contract cases was not explicitly regulated in Indonesian Civil Code.  However, Supreme Court through its Jurisprudences Number 1503 K/Pdt/2001 and Number 2822 K/Pdt/2014 accept creditor’s claim for the immaterial losses and broaden the meaning of immaterial losses in breach of contract cases. The fulfillment for the immaterial losses in these cases focuses on the combination of the objectivity and subjectivity of the Judges, reflect on the fundamental factors related to the case and base their decision on the ex-aquo et bono principle.